Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1159/000102899
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A Injection in ISDN Ointment-Resistant Chronic Anal Fissures

Abstract: Background: In the treatment of chronic anal fissures (CAFs), surgical sphincterotomy is more commonly being replaced by chemical sphincterotomy. After the good results of our pilot study including 32 patients, we now describe the effect of botulinum toxin A (BT-A) in a consecutive series of 100 patients with isosorbide dinitrate (ISDN) ointment-resistant CAFs. Methods: From October 2002 until August 2005, 100 patients (52 males, 48 females) with a median age of 45 (20–79) years were treated with an injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
2
17
1
Order By: Relevance
“…Although the exact pathogenesis of anal fissure is still unclear, based on recent studies, a local ischemia seems to play a crucial role in the pathogenesis. The increased resting anal tone of internal sphincter muscle influences prolonged compression of anodermal arteries passing through the muscle, resulting in local ischemia [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the exact pathogenesis of anal fissure is still unclear, based on recent studies, a local ischemia seems to play a crucial role in the pathogenesis. The increased resting anal tone of internal sphincter muscle influences prolonged compression of anodermal arteries passing through the muscle, resulting in local ischemia [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…47 Almost 4% of the patients discontinued the therapy and were switched to DIL. GTN therapy was discontinued because of headache (four patients) and pruritus ani (three patients).…”
Section: Discussionmentioning
confidence: 99%
“…When the DIL is heated, the relaxing effect is enhanced. 45 Short-term healing rates are reported as high as 95% when used in combination with GTN, [46][47][48][49] with about 10% reduction after 2 years follow-up. Recently, Schiano et al reported healing rates of 75% with DIL only and 93.7% with combined GTN/DIL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we found that the effect of botulinum toxin A injections was higher if initial nonresponders were retreated [1]. Therefore, all patients included in this study had undergone at least one botulinum toxin A injection; 11 patients had an injection of 60IE (0.3 ml) and 10 patients received 80IE (0.4 ml) as a first injection dosage.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, all patients included in this study had undergone at least one botulinum toxin A injection; 11 patients had an injection of 60IE (0.3 ml) and 10 patients received 80IE (0.4 ml) as a first injection dosage. The different first injection dosage of Dysport used was a result of changing our treatment policy from 60IE to 80IE Dysport in the latter years because even with this higher dosage, no continence problems were experienced [1]. Eight patients had received a second injection with 80IE and one patient four injections (each 80IE) before enrolling in this study.…”
Section: Methodsmentioning
confidence: 99%